Rubi Capenses: a further contribution to the knowledge of the genus Rubus (Rosaceae) in South Africa - van De Beek, Abraham (Phytotaxa, 2021)
This article is aimed to provide a solid base for future research in Rubus in South Africa. Even if a different classification using a broader species concept will be adopted later, this contribution should be valuable for identifying the units and naming them for convenience of all later analyses. Types of earlier published names were checked and compared with present occurrence of Rubus in the region. When needed, types where designated. Some taxa where provided with a new name or status. New taxa were described if they are taxonomically well distinguished and have a solid geographical distribution. This paper contains the following nomenclatural novelties: New taxa: Rubus ser. Apetali, R. ser. Pinnati, R. ser. Rigidi, R. ser. Scleri, R. anas, R. ×bergianus, R. cryptopetalus, R. fertilis, R. ×fultiformis, R. ×fultus, R. leptodytus, R. noli-tangere, and R. trichogynus. New status and names: R. cacoeimon and R. leptostelechus. Replacement names: R. glabrior, and R. thaumasius. New status: Rubus subsect. Afroidaei and R. subsect. Pinnatifidi. New types are designated for the following taxa: R. ser. Piletocaulon, R. ser. Tephrocaulon, R. sect. Afromontani, R. borbonicus, R. borbonicus f. pyramidalis, R. exsuccus, R. heterophyllus, R. inedulis, R. madagascarius, R. originalis, R. pappei, R. pinnatus, R. pinnatus f. glaber, R. quartinianus, and R. rigidus f. umbrosus.